Quick Access to Pyridines through 6π-3-Azatriene Electrocyclization: Concise Total Synthesis of Suaveoline Alkaloids - Wei, Hongbo; Li, Yun (Synlett, 2019)
Pyridine is a prevalent structural heterocyclic motifs in natural products, pharmaceuticals, and advanced materials. Several different methodologies have been developed for the synthesis of these kinds of molecules. However, a sustainable and efficient procedure for the synthesis of pyridines is still highly desirable. In this Synpacts article, we highlight our recent approach to the construction of highly substituted pyridines though a tandem condensation/alkyne isomerization/6π-3-azatriene electrocyclization sequence. The present protocol was used to synthesize a series of polysubstituted pyridines (30 examples) in moderate to good yields. The process also permitted the development of a concise strategy for collective total syntheses of suaveoline, norsuaveoline, and macrophylline.
Keywords: pyridines; alkaloids; 6π-electrocyclization; total synthesis; tandem reaction